KETAHANAN DAN KEMANDIRIAN PANGAN RUMAH TANGGA PETANI PADI DI DAERAH RAWAN PANGAN KECAMATAN PAGELARAN UTARA KABUPATEN PRINGSEWU - Titis Widyawati Sholeha; Fembriarti Erry Prasmatiwi; Dyah Aring Hepiana Lestari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purposes of this research are to analyze the level of food security, the factors that affect the level of food security, and food self-suffiency of paddy households.  North Pagelaran is chosen purposively as research location for the location is food insecure area.  The respondents consist of fourty paddy household were selected by simple random sampling.  The result of this research showed that the majority of household is classified as less food (47.50%), as food secure (22.50%) and the rest respondents classified as vulnerable food and food insecured (17.50% and 12.50%).  The factors that affected the level of food security were the level formal education of housewives, paddy field, in addition to rice and egg price.  Households food self-suffiency in North Pagelaran distric has classified as high food self-suffiency.  Key words: Food insecure area, food security, food self-suffiency, paddy households